An Inclusive Approach to Cultural Heritage Audiences – The Case of Porta Posnania - Perska, Anita; Stefańska, Magdalena (Inkluzywne podejście wobec odbiorców dziedzictwa kulturowego – przykład Bramy Poznania, 2024)
Aim: The objective of this article is to identify and assess inclusive solutions for accessibility for people with special needs, exemplified by Porta Posnania – the first heritage interpretation centre in Poland. Methodology: In order to achieve this objective, the following methods were employed: analysis of literature relevant to the subject area, development of a case study, an individual in-depth interview with the manager of the cultural institution, and an analysis of documents and the institution’s website. Results: By building its cultural offering, Porta Posnania, under the management of the Poznań Heritage Centre, ensures architectural, digital, informational, and communicational accessibility, as well as alternative access through technological support. These efforts contribute to the implementation of sustainable development goals related to DEI (diversity, equity, and inclusion). The measures taken to ensure accessibility target people with special needs, including, individuals with visual impairments, hearing impairments, intellectual disabilities, mobility impairments, and neurodiverse individuals. Implications and recommendations: This study offers several avenues for further research, including the following: identification of factors influencing the satisfaction of individuals with special needs when using cultural services, and identification of barriers to accessing cultural services for people with special needs. Originality/value: This study fills the research gap related to the management of inclusivity in cultural facilities situated near sites of historical and natural importance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 4, s. 75-85
Keywords: social inclusion; DEI; inclusiveness; heritage interpretation centre; Sustainable Development Goals; włączenie społeczne; inkluzywność; centrum interpretacji dziedzictwa; cele zrównoważonego rozwoju